Stylistic Analysis of Francis Bacon’s Selected Essays - Khaled Ahmad Sarwary Ahmad; Zalmai Samsor (Randwick International of Education and Linguistics Science Journal, 2024)
This paper is an attempt to analyze stylistically Bacon’s essays. The main purpose of this study is to analyze the writing style of Francis Bacon in the following selected essays (Of Studies, Of Revenge, OF Ambition, and Of Marriage and Single Live). Researchers analyzed the writing style of Bacon in these essays, specifically the aphoristic style. One of the most crucial characteristics of Bacon’s essays style is aphorism. It is a style which specified by direct, straightforward, pithy and concise language. Apart from this, utilitarianism which is another feature of Bacon’s essays style, has been clarified clearly. Utilitarianism is a philosophy of thought that maintain and support that the foremost actions are those that create the most happiness for the greatest number of people. In fact, researchers have found some elements regarding the selected essays such as didacticism, mannerism as well as worldly wisdom that introduce Francis Bacon as utilitarian writer. Moreover, other crucial elements of Bacon’s essays such as quotations, impersonality, as well as paragraph have been analyzed very briefly in this paper. Actually, this study is based on qualitative research. Research design was the textual analysis in order to analyze the text. The main instrument was the text of Francis Bacon’s selected essays. The data were in the form of lines, sentences, phrases and words. To analyze the text, the researchers have used steps such as paraphrasing, analyzing, identification and classification. Finally, the result of this study shows the writing style of Francis Bacon which is based on the aphoristic, utilitarianism and other significant elements, like usage of impressive quotations, unique paragraph and Bacon’s objectivity regarding to his essays.